Analisis Kesuksesan Aplikasi Presensi Mobile QR Code Universitas Muhammadiyah Purwokerto Menggunakan Model DeLone dan McLean - Putri, Eno Sukarno; Harjono, Harjono (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
Universitas Muhammadiyah Purwokerto (UMP) has adopted QR Code technology for its student attendance application. However, it is important to evaluate the success and performance of the application. This study aims to determine the level of success and factors that drive the success of the UMP Attendance application. The DeLone and McLean (2003) model uses 6 variables as a research evaluation framework. The research method used is quantitative with an associative approach and uses the SEM-PLS model assisted by SmartPLS 4.1.0.6 software in analyzing data. This research was conducted at Muhammadiyah Purwokerto University with 99 respondents who were active undergraduate students of UMP. The results showed that the implementation of the UMP Presence Application was considered quite successful and successful based on the DeLone and McLean (2003) SI success model. Judging from the aspects of system quality and information quality, it is strong enough to encourage use, user satisfaction and net benefits. However, it is necessary to improve the quality of service to users. So that later it will also affect the increase in use and provide benefits for users of the UMP Presence Application itself.